2013
DOI: 10.3897/zookeys.277.3942
|View full text |Cite
|
Sign up to set email alerts
|

Barucynips panamensis, a new genus and species of oak gallwasps (Hymenoptera, Cynipidae, Cynipini) from Panama, and description of one new species of Coffeikokkos

Abstract: Barucynips panamensis Medianero & Nieves-Aldrey, a new genus and species of oak gallwasps (Hymenoptera: Cynipidae: Cynipini), is described from adults reared from galls on Quercus bumelioides in Panama. The new genus is taxonomically close to the recently described Coffeikokkos from Costa Rica, but differs from it and all of the described genera of Cynipini, by the shape and setation of the projecting part of the ventral spine of the hypopygium and by the sculpture of the propodeum. A new species of Coffeikokk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Studies over the last decade have revealed new morphological diversity in Neotropical oak-associated cynipids; around 100 species of Nearctic and Neotropical Cynipidae have been described or revised, primarily associated with red oaks (Quercus section Lobatae) and white oaks (Quercus section Quercus; see for example Pujade-Villar et al 2010, Pujade-Villar et al 2012a, Pujade-Villar et al 2012b, Pujade-Villar et al 2013, Medianero & Nieves-Aldrey 2013, Pujade-Villar et al 2014, Nicholls et al 2018b, Cuesta-Porta et al 2020. Incorporating this novel morphological diversity into the existing generic level classification has been a challenge because some taxa show combinations of characters otherwise diagnostic of different genera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies over the last decade have revealed new morphological diversity in Neotropical oak-associated cynipids; around 100 species of Nearctic and Neotropical Cynipidae have been described or revised, primarily associated with red oaks (Quercus section Lobatae) and white oaks (Quercus section Quercus; see for example Pujade-Villar et al 2010, Pujade-Villar et al 2012a, Pujade-Villar et al 2012b, Pujade-Villar et al 2013, Medianero & Nieves-Aldrey 2013, Pujade-Villar et al 2014, Nicholls et al 2018b, Cuesta-Porta et al 2020. Incorporating this novel morphological diversity into the existing generic level classification has been a challenge because some taxa show combinations of characters otherwise diagnostic of different genera.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, significant new faunas of oak gall wasps have been discovered in the Neotropical and Oriental regions, leading to the description or re-establishment of 17 genera. Eight of the recently described genera belong to the American fauna; two are endemic to Central America, Coffeikokkos Pujade-Villar & Melika (Pujade-Villar et al 2012b) and Barucynips Medianero & Nieves-Aldrey (Medianero & Nieves-Aldrey 2013); one, Protobalandricus Melika, Nicholls & Stone, is known only from California (Nicholls et al 2018b); and five genera are more widely distributed in North America and Central America: Kinseyella Pujade-Villar & Melika (Pujade-Villar et al 2010), Zapatella Pujade-Villar & Melika (Pujade-Villar et al 2012a), Kokkocynips Pujade-Villar & Melika (Pujade-Villar et al 2013), Melikaiella Pujade-Villar (Pujade-Villar et al 2014) and Striatoandricus Pujade-Villar (Cuesta-Porta et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prokius gen. nov. is the fourth recently described cynipid genus that is endemic to the Central American section of the Neotropical region, after Barucynips, Coffeikokkos and the inquiline genus Agastoroxenia, (Nieves-Aldrey & Medianero 2010, Pujade-Villar et al 2012, Medianero & Nieves-Aldrey 2013. The gall wasp fauna of this geographical region has traditionally been very poorly studied.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Medianero & Nieves-Aldrey (2011) listed eight genera of native Cynipini from this region: Acraspis Mayr, 1881, Amphibolips Reinhard, 1865, Andricus Hartig, 1840, Atrusca Kinsey, 1930, Bassettia Ashmead, 1887, Disholcaspis Dalla Torre & Kieffer, 1910, Loxaulus Mayr, 1881and Odontocynips Kieffer, 1910. Since then, species from seven more genera have been recorded: Coffeikokkos Pujade-Villar & Melika, 2012(Pujade-Villar et al 2012b, Medianero & Nieves-Aldrey 2013, Barucynips Medianero & Nieves-Aldrey, 2013 (Medianero & Nieves-Aldrey 2013), Striatoandricus Pujade-Villar, 2020 (Medianero & Nieves-Aldrey 2019, Cuesta-Porta et al 2020, Melikaiella Pujade-Villar, 2014 (Medianero & Nieves-Aldrey 2014), Neuroterus Hartig,1840 (Medianero & Nieves-Aldrey 2017), Zapatella Pujade-Villar & Melika, 2012(Pujade-Villar et al 2012a and Kokkocynips Pujade-Villar & Melika, 2013(Nieves-Aldrey et al 2021; this brings the total number of genera of oak gall wasps currently known from the Neotropical region to 15. However, our sampling has revealed further taxa from this region that are morphologically and genetically distinct from known Cynipini genera and hence require formal description.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, important faunas of oak gall wasps from the Neotropical and Oriental regions have been discovered and are being studied, mainly those from Japan (Ide et al , 2012(Ide et al , 2013 and Taiwan (Melika et al , 2013Tang et al 2011a, b) and those from Panama and Costa Rica (see Medianero & Nieves-Aldrey 2011 for an updated list of the Cynipidae of the Neotropical region). In the above-mentioned list, 17 species of cynipini in 9 genera were recorded, but the list has been enlarged since then with the addition of 2 new genera and species (Pujade-Villar et al 2012;Medianero & Nieves-Aldrey 2013).…”
mentioning
confidence: 99%